Establishment and Evaluation of a Rat Model of Sidestream Cigarette Smoke-Induced Chronic Obstructive Pulmonary Disease - Wang, Genfa; Mohammadtursun, Nabijan; Sun, Jing; Lv, Yubao; Jin, Hualiang; Lin, Jinpei; Kong, Lingwen; Zhao, Zhengxiao; Zhang, Hongying; Dong, Jingcheng (Frontiers in Physiology, 2018)
Chronic obstructive pulmonary disease (COPD) is a common cause of mortality worldwide. The current lack of an animal model that can be established within a certain time frame and imitate the unique features of the disease is a major limiting factor in its study. The present study established and evaluated an animal model of COPD that represents the early and advanced stage features using short-, middle-, and long-term sidestream cigarette smoke (CS) exposure. One hundred and nine Sprague–Dawley rats were randomly divided into 10 groups for different periods of sidestream CS exposure or no exposure (i.e., normal groups). The rats were exposed to CS from 3R4F cigarettes in an exposure chamber. Histological analysis was performed to determine pathological changes. We also conducted open-field tests, lung function evaluations, and cytokine analysis of the blood serum, bronchoalveolar lavage fluid, and lung tissue. The lung tissue protein levels, blood gases, and computed tomography images were also analysed. As the CS exposure time increased, the indicators associated with oxidative stress, inflammatory responses, and airway remodelling were greater in the CS exposure groups than in the normal group. At 24 and 36 weeks, the COPD model rats displayed the middle- and advanced-stage features of COPD, respectively. In the 8-week CS exposure group, after the CS exposure was stopped for 4 weeks, inflammatory responses and oxidative responses were ameliorated and lung function exacerbation was reduced compared with the 12-week CS exposure group. Therefore, we established a more adequate rat model of sidestream CS COPD, which will have great significance for a better understanding of the pathogenesis of the disease and evaluation of drug effectiveness.